1970
DOI: 10.1002/bjs.1800570702
|View full text |Cite
|
Sign up to set email alerts
|

One hundred consecutive cases of complete prolapse of the rectum treated by operation

Abstract: One hundred patients, 17 male and 83 female, ranging in age from a few days to 97 years , have been treated between 1955 and 1969 for complete prolapse of the rectum.2. One hundred and twelve operations were performed, 91 by the abdominal route, mostly Roscoe Graham repairs or Ivalon sponge implants, with only 2 immediate deaths.3. The late results were assessed usually by interview and physical examination 6 months to 14 years (mean 5 years 5 months) postoperatively. Seventyfive of the patients who had had ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
9

Year Published

1972
1972
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 9 publications
0
23
0
9
Order By: Relevance
“…Rarely uterine prolapse can be manifested along with rectal prolapse. 2,7,8 Prolapse refers to "the falling down or slipping of a body part from its usual position or relations". It is derived from the Latin pro--"forward" + labi -"to slide".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely uterine prolapse can be manifested along with rectal prolapse. 2,7,8 Prolapse refers to "the falling down or slipping of a body part from its usual position or relations". It is derived from the Latin pro--"forward" + labi -"to slide".…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Vaginal hysterectomy with pelvic floor repair, followed by repair of rectal prolapse by Delorme method is a best approach.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Efficacy of simple suture rectopexy is time tested with recurrence rate varying from 4-10% [9]. Experience of various operators on reexploration of pelvis after low anterior resection revealed that dense post operative fibrosis fixes rectum to the sacral hollow [2].…”
Section: Discussionmentioning
confidence: 99%
“…Placement of sutures between bladder base and anterior rectal wall provides additional support and prevents initiation of sliding herniation of anterior rectal wall which later develops into full procendentia [9]. Limited 3 inch approx.…”
Section: Discussionmentioning
confidence: 99%
“…Wohl ist auch hier die Diagnose durch den Nachwcis prolabicrcnder zirkul~rer Schleimhautfaltcn, mindcstens bcim PrcBakt, vSllig klar. Dieser Befund stellt aber bereits das Endstadium einer mehr oder weniger protrahierten Entwicklung dar; FremdkSrpergeffihl oder Druck im Rectum, das Geffihl der unvollst/~ndigen Entlecrung verbunden mit Tencsmcn oder schlieBlich einmal Schleim-und Blutabg/inge infolge Irritation der Schlcimhaut sind unspezifische Friihsymptome [3,17,23]. Die chronischc…”
unclassified